Data communications and networking - Farouzan, Behrouz A. (McGraw-Hill Forouzan networking series., 2013)
Suitable for international computer networks students, this title presents an accessible approach to data communications and networking. It contains 830 figures and 150 tables to provide a visual and intuitive opportunity for understanding the material.